(untitled) (Scientific journal of the Fergana State University, 2023)
At the end of the 20th and the beginning of the 21st century, the Arab Republic of Egypt, both in domestic and foreign policy, fought against religious extremism, radicalism and terrorism, which posed a great threat to the security and stability of the country. The article analyzes the features of the fight against religious extremism and terrorism in the regional security policy of Egypt during the presidency of Hosni Mubarak and Abdel Fattah al-Sisi.